Photoinduced degradation of methylammonium lead triiodide perovskite semiconductors. Issue 41 (7th October 2016) - Tang, Xiaofeng; Brandl, Marco; May, Benjamin; Levchuk, Ievgen; Hou, Yi; Richter, Moses; Chen, Haiwei; Chen, Shi; Kahmann, Simon; Osvet, Andres; Maier, Florian; Steinrück, Hans-Peter; et al.
Abstract : Photoinduced degradation mechanisms of CH3 NH3 PbI3 thin films under vacuum and in air are reported. Abstract : Photoinduced degradation is a critical obstacle for the real application of novel semiconductors for photovoltaic applications. In this paper, the photoinduced degradation of CH3 NH3 PbI3 in a vacuum and air (relative humidity 40%) is analyzed by ex situ and advanced in situ technologies. Without light illumination, CH3 NH3 PbI3 films slowly degrade under vacuum and air within 24 hours. However, we find that CH3 NH3 PbI3 converts to metallic lead (Pb 0 ) when exposed to vacuum and light illumination. Further, a series of lead salts ( e.g. PbO, Pb(OH)2 and PbCO3 ) are formed when CH3 NH3 PbI3 is degraded under environmental conditions, i.e. under the combination of light, oxygen and moisture. Photoinduced degradation is found to be determined by the environmental atmosphere as CH3 NH3 PbI3 films remain very stable under nitrogen conditions. The results from vacuum conditions underpin that the high volatility of the organic component (CH3 NH3 I) is in conflict with reaching excellent intrinsic stability due to its role in creating ion vacancies. The degradation in air suggests that both oxygen and water contribute to the fast photodecomposition of CH3 NH3 PbI3 into lead salts rather than water alone. Given these basic yet fundamental understandings, the design of hydrophobic capping layers becomes one prerequisite towards long-term stable perovskite-based devices.